Cryptocurrency vs fiat currency: Architecture, algorithm, cashflow & ledger technology on emerging economy subtitle: The influential facts of cryptocurrency and fiat currency - Rabiul Islam, Mohammad; Taha Alshaikhli, Imad Fakhri; Mohd. Nor, Rizal; Mohammad, Kabir Sardar (IEEE, 2018)
Typically, electronic currency like digital or cryptocurrency both are influencing the world economy under the ledger technology, where as traditional fiat currency plays vital role in socio economy followed by conventional printing method. This review paper is basically focused on most influential facts behind the economical elements like the applicable operation via successful blockchain algorithm, architecture and mining operation based on contents from journal publications, online publications, news reports, seminars and workshops. Several aspects of crypto and fiat currencies are rolling on emergingeconomy, from this point, this paper tries to figure out how consensus algorithm and growing numbers of crypto and fiat currencies are performed with its existing pros and cons towards further developing process.